Induction of flowering by seasonal changes in photoperiod - Searle, Iain (2004)
In many plants, major developmental transitions such as the initiation of flowering are synchronized to the changing seasons. Day length provides one of the environmental cues used to achieve this. We describe the molecular mechanisms that measure day length and control flowering in Arabidopsis. Also, we compare these mechanisms with those that control flowering time in rice. This comparison suggests that components of the Arabidopsis regulatory network are conserved in other species, but that their regulation can be altered to generate different phenotypic responses.